Pengembangan Model Pembelajaran Discovery Learning Yang Diintegrasikan dengan Model Experiental Learning Berbasis Google Meet untuk Meningkatkan Keterampilan Siswa pada Mata Pelajaran Fikih di UPT SDN 060932 - Siti Qomariah; Predi Ari Repi; Misra Nova Dayantri; Radhinal Abdullah; Tri Abdi Syahputra; Wahyuddin Nur Nasution (EduInovasi: Journal of Basic Educational Studies, 2025)
The teaching of Fiqh at UPT SDN 060932 still relies on one-way lecture methods, resulting in passive students, low learning motivation, and suboptimal learning outcomes. The lack of technological innovation in learning, especially in online learning, exacerbates this situation. This study employs the Research and Development method according to Sugiyono, using the Borg & Gall model, to develop a Discovery Learning model integrated with Experiential Learning based on Google Meet. The results show that this model is effective in improving student learning outcomes, as evidenced by an average formative test score of 91, which exceeds the minimum passing grade (75). The development of this model is recommended to be continued to encourage more active and skilled students, and further research is needed to explore its potential in enhancing the quality of Fiqh learning.